Analytical categories to describe deficit attributions in deep disagreements between citizens and experts. (January 2022) - Fuentes, Claudio; "Iñaki" Goñi, Julian; Miranda, Constanza
Disagreements often arise from citizen–expert collaboration, as both agents share a different epistemic worldview. Fogelin, following Wittgenstein, proposed that some disagreements (i.e. deep disagreements) cannot be rationally solved when participants share different forms of life. Citizen–expert is an exemplar of this sort of disagreement. Moreover, deep disagreements are often followed by deficit attributions from one of the agents to the other, regarding their epistemic understanding, credibility, and motives. Articulating the notions of deep disagreements and deficit attributions, as well as reviewing the complementary concept of epistemic injustice, we have constructed analytical categories that allow us to understand two things: (1) how deficit attributions operate in dialogical contexts of deep disagreements and (2) what types of deficit attributions we can find. We expect that this characterization can serve to analyze citizen–expert dialogues and the pursuit of more modest and inclusive forms of conversation.